(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

y''+2y'+y = 4t^2 - 3 + (e^-t)/t

of course i evaluated the general soltuion to be c1e^-1t + c2te^-1t

but now how do you do the right part? i tried y=At^2+Bt+c+1/(Dt+E)*e^-t as a solution but after differentiating it twice and putting it into the eqaution i got...

(4e^t/Dt+E)-(4De^t/(Dt+E^2))+(2D^2e^t/(Dt+E)^3)+At^2+4At+Bt+2A+2B+C = 4t^2-3+(e^-t)/t

and i don't know what to do with that. i found a=4 and b=0 and c=-11 but that's about all i did, i'm unsure how to find the rest of the letters to complete the probleme

2. Relevant equations

3. The attempt at a solution

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Superposition and variation of parameters

**Physics Forums | Science Articles, Homework Help, Discussion**